Pityriasis Rubra Pilaris After Moderna COVID-19 Vaccination: A Case Report and Literature Review. (10th March 2023) - Liu, Yi A.; Dai, Julia; Nagarajan, Priyadharsini; Torres-Cabala, Carlos A.; Aung, Phyu P.; Prieto, Victor G.; Cho, Woo Cheal
Abstract: To date, over 60% of the world's population has received at least 1 dose of coronavirus disease 2019 (COVID-19) vaccination, with over 12 billion doses administered globally. Commonly reported adverse effects of COVID-19 vaccination include fever, headache, myalgia, and injection site reactions. The spectrum of documented cutaneous reactions after COVID-19 vaccination is broad; however, pityriasis rubra pilaris (PRP) or PRP-like eruption secondary to COVID-19 vaccine is exceedingly rare, with only 17 cases previously reported to date in the English literature. In this article, we describe an additional case of COVID-19 vaccination-associated PRP in a 50-year-old woman with a history of metastatic breast carcinoma, who developed a widespread cutaneous eruption characteristic of PRP, including palmoplantar keratoderma, 10 days after her third dose of Moderna COVID-19 vaccine. Punch biopsy specimen showed epidermal hyperplasia with overlying hyperkeratosis, alternating orthokeratosis and parakeratosis and focal follicular plugging, supporting the diagnosis of PRP. The patient improved within weeks of initiating oral acitretin and topical steroids, with resolution achieved after 3 months of continued therapy. To the best of our knowledge, this is the third reported case of Moderna COVID-19 vaccination-associated PRP and collectively the 18 th after the administration of all COVID-19 vaccines currently available, including Pfizer–BioNTech, and AstraZeneca.